BMI upon discharge from hospital and its relationship with survival: an observational study utilising linked patient records. (June 2016) - Freemantle, Nick; Ray, Daniel; Falcaro, Milena; McNulty, David; Shallcross, Laura; Wood, John; Pagano, Domenico
Objective: Current advice for patients being discharged from hospital suggests a body mass index of 18.5 to 24 kgm −2, although this aspirational target may often not be achieved. We examined the relationship between body mass index on discharge from hospital and subsequent mortality over a maximum follow-up of 3.8 years. Design: We conducted a survival analysis using linked hospital records data with national hospital episode statistics and national death certification data. Participants & Setting: The analysis included adult patients who were admitted to University Hospitals Birmingham NHS Foundation Trust for a period of over 24 h during 2011, excluding day cases and regular day case attenders. Main outcome measures: The relationship between body mass index and mortality at medium term was estimated separately in both men and women, after accounting for case-mix. Results: For both males and females, the relationship between body mass index at discharge and the loge hazard of death was strongly non-linear (p = 0.0002 for females and p < 0.0001 for males) and predictive (both p < 0.0001). In all models, the optimal body mass index range associated with best survival was 25 to 35 kgm −2, with a sharp increase in risk for lower body mass index. Conclusions: There was little evidence to support current aspirational body mass index targets in the discharge population. Hospitals should ensure adequate nutrition especially among those with a reduced body mass index.